ANALISIS KEBIJAKAN KEMENAG 2024 - 2029 UNTUK PTKI YANG BERDAYA SAING, INKLUSIF DAN BERINTEGRITAS - Adi Sanusi; Oki Setiana Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic education constitutes an integral part of the national education system and plays a strategic role in developing human resources who possess faith, piety, noble character, and adequate academic competence. This study aims to analyze the regulations and policies governing Islamic education in Indonesia and their implications for the development of Islamic educational institutions. The research employs a library research method with a descriptive qualitative approach. Data were collected from various primary and secondary sources, including legislation, scholarly books, academic journals, and official documents related to Islamic education. The findings indicate that the Indonesian government has demonstrated significant commitment to the development of Islamic education through various regulations and policies governing madrasahs, Islamic boarding schools (pesantren), and Islamic higher education institutions. These policies are directed toward improving educational quality, expanding access to education, strengthening institutional governance, and adapting Islamic education to the advancement of science and technology. Nevertheless, policy implementation continues to face several challenges, including disparities in institutional quality, limitations in human resources, and the need to adapt to global developments. Therefore, synergy among the government, educational institutions, and society is required to realize a high-quality, competitive Islamic education system that remains grounded in Islamic values.